DIAGNOSIS INFRASTRUCTURE FOR SOFTWAREHARDWARE SYSTEMS - Khahanov, V. I.; Chumachenko, S. V.; Litvinova, Y. I.; Guz, O. A. (Radio Electronics, Computer Science, Control, 2012)
An infrastructure and technologies for analyzing cyberspace are proposed. A transactional graph model and method for diagnosing digital systems-on-chips, focused to considerable reducing the time of fault detection and memory for storing the diagnosis matrix by forming ternary relations in the form of test, monitor, functional component, are created.